Establishing a National Quality of Care Framework for Heart Failure in Korea: Keep Standards for Heart Failure (KSHF) Initiative - Jung, Mi-Hyang; Lee, Soo Yong; Cho, Yang Hyun; Bae, Dae-Hwan; Lee, Sunki; Lee, Chan Joo; Son, Jung-Woo; Cho, Jae Yeong; Kim, Eung Ju (International journal of heart failure, 2025)
Heart failure (HF) continues to pose a significant public health burden in Korea, marked by increasing prevalence, hospitalizations, and healthcare costs. Although advances in guideline-directed medical therapy (GDMT) have improved patient prognosis, a persistent gap between evidence-based guidelines and real-world practice hinders optimal patient outcomes. To address this challenge, the Korean Society of Heart Failure launched the Keep Standards for Heart Failure (KSHF) initiative to enhance the quality of care (QoC) for individuals with HF. This initiative combines registry-based and non-registry approaches, including the development of structured educational programs, a standardized discharge checklist, and the implementation of the KSHF-QoC registry. The registry is designed to systematically evaluate HF management across diverse healthcare settings by analyzing prescription trends, treatment adherence, and patient-centered outcomes. Unlike earlier registries that focused primarily on acute HF in tertiary care centers managed by HF specialists, the KSHF-QoC registry broadens its scope to include general cardiologists, thereby offering a more comprehensive and representative assessment of routine care. Through continuous monitoring of QoC indicators, benchmarking across institutions, and structured performance feedback, the KSHF initiative aims to improve GDMT adherence, optimize HF care delivery, and reduce readmission rates. These efforts represent a critical advancement toward standardizing HF management and improving long-term outcomes for patients in Korea.